Errors in the administration of intravenous medications in patients undergoing anesthesia in the operating room - Juan David Miranda; Lorena Vallejos; Diana Patricia Ñañez; Jose Andres Calvache (Revista de la Facultad de Ciencias de la Salud, 2013)
Errors in medication administration have affected the anesthetic practice over the time and have become a major cause of perioperative morbidity and mortality. Among different medical specialties, anesthesiology is perhaps the most likely to make mistakes in this procedure. This is because in many places around the world, a single professional "anesthesiologist" orders, prepares and administers a drug at one time and setting. For thirty years, Cooper disclosed the first reports of critical incidents and perioperative safety scheme, and in the 90s', Chopra performed a retrospective analysis, found that medication errors are the fourth most common that results in disability in 17% and death in 8%, these being preventable errors in 51% of cases. It’s essential for the safe practice of anesthesia to establish interventions for improving prevention programs, education, research and development, enabling break traditional paradigms, with the aim of making recommendations and standardize the safe administration of drugs in this field.